ANALISIS PENGARUH ASPEK KEPERILAKUAN TERHADAP SISTEM AKUNTANSI (Studi Pada PT. XXX) - Dwi Probonurtjahjo; Rixky Dodik Eko Saputra; Ajeng Trimartalia; Asep Wildan (Sekolah Tinggi Ilmu Ekonomi Yapan, 2018)
ABSTRACTThis study aims to determine the effect of attitudes towards the use of accounting systems at PT. XXX, to determine the effect of motivation on the use of accounting systems at PT. XXX, to determine the effect of emotions on system usage accounting at PT. XXX, to determine the effect of the perception of the use of the accounting system at PT. XXX. This study is a correlational study or the relationship between the independent variables on the dependent variable and the analysis unit that is considered to be employees who have worked more than 6 months who have undergone a training period of 40 people. The questionnaire tested its validity and reliability before testing the research data, the test equipment used in this study used the classical assumption test which included normality test, linearity test, heteroscedasticity test and multicollinearity test, the data analysis method used was multiple linear regression analysis using a tool of analysis in SPSS 25 statistics. The results of this study indicate that attitude variables do not significantly influence the use of accounting systems, the motivation variable does not significantly influence the use of accounting systems, emotional variables have a significant effect on the use of accounting systems and perception variables do not significantly influence the use of accounting systems.Keywords : attitude, motivation, emotion, perception, use of the accounting system.